Synthesis of guanosine and its derivatives from 5-amino-1-beta-D-ribofuranosyl-4-imidazolecarboxamide. III. Formation of a novel cycloimidazole nucleoside and its cleavage reactions. - Okutsu, M (1976)
A new cycloimidazole nucleoside, 5-(1 inch -benzamido-1 inch-hydroxymethylene) amino-2', 1 inch-anhydro-1-beta-D-ribofuranosyl-4-imidazolecarboxamide (III) was synthesized by reaction of 5-amino-1-beta-D-ribofuranosyl-4-imidazolecarboxamide (AICA-riboside) with benzoyl isothiocyanate followed by methylation with methyl iodide. The structure of III was elucidated on the basis of its nmr spectra and chemical reactions. Of special interest are reactions of III with various nucleophiles. For example, guanosine (IX) was obtained by amination of III wtih ammonia in 72% yield. Analogous reactions of III with methylamine and dimethylamine gave N2-methylguanosine (X) and N2-dimethylguanosine (XI), respectively. Refluxing of III in alkaline solution afforded xanthosine (VII). The probable mechanism of formation and facile ring-opening of III is also discussed.